Prediction of Overpressure Zones in Marine Sediments Using Rock-Physics and Other Approaches - Nikita Dubinya; Irina Bayuk; Alexei Hortov; Konstantin Myatchin; Anastasia Pirogova; Pavel Shchuplov (Journal of Marine Science and Engineering, 2022)
The paper discusses the problem of localizing zones of high pore pressure in sub-bottom sediments (first tens of meters under the seafloor). Prediction of the overpressure zones in the near-surface is required for the mitigation of risks at the early stages of the offshore hydrocarbon field exploration and development. The results of seismic data interpretation generally serve as the main source of information for this kind of problems, yet there are other methods to predict overpressure zones in the subsurface. The paper presents the results of the overpressure zone prediction using a set of methods including empirical ones, and the approach based on rock-physics modeling that features the soft-sand model of unconsolidated media effective properties. While the rock-physics modeling grants the most reliable result, it is also the most demanding method to the input data. Hence, it can be used to verify other methods of the overpressure zone prediction. We present the results of the overpressure zone prediction at the research site on the Black Sea shelf. The mitigation of the drilling risks via changing the drilling conditions is discussed in detail. As the drilling through the overpressure zones is often a necessity, the engineering solutions proposed in the paper can be applied elsewhere when facing similar problems typical for offshore exploration.